Preventive Effect of Glycine on 5-FU-Induced Oral Mucositis in Rats (Histological and Immunohistochemical Study) (Indian Journal of Forensic Medicine & Toxicology, 2020)
OM is the most popular side effects of chemotherapy and it’s commonly caused by 5-Fluorouracil (5-FU).This study was aimed to assess the impact of glycine as a new option of treatment on experimentally inducedoral mucositis in adult male rats.Thirty two male rats (Rattus novergicus) were divided at random in to control group (8 rats), 5-FU untreatedgroup and 5-FU-glycine treated group (12 animals each). OM model induced by chemotherapy was institutedby intraperitoneal injection of 5-FU (60 mg\kg body weight) on days 0, 5, 10, 15 and the dorsal tongue wasscratched (days 3, 4) by needle with gauge 18 to induce mucositis. The rats in treated group were receiveda 2mg\g intraperitoneal injection of 5% glycine daily (day 0-20). All rats were scarified at day 21, dorsaltongue mucosa sample was removed, prepared and examine by using histological and immunohistochemical(PCNA and BCL-2 immunostining) analysis. Glycine can protect the dorsal tongue mucosa from 5-FUinduced cytotoxicity and alleviated the associated damage. In 5-FU/glycine group, both of the PCNA andBCL-2 immune expression was significantly increased (p?0.05) in comparison with 5-FU untreated group.Glycine provides protection toward 5-Fluorouracil induced tongue mucositis. It show fast epithelialpropagation and wound healing through its antioxidant, anti-inflammatory and cytoprotective features.